Photoelastic analysis to compare implant-retained and conventional obturator dentures - Goiato, Marcelo Coelho [UNESP]; Ribeiro, Paula do Prado [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Haddad, Marcela Filie [UNESP]; Santos, Daniela Micheline dos [UNESP]; Moreno, Amalia [UNESP] (Spie-soc Photo-optical Instrumentation Engineers, 2012)
The use of photoelastic analysis contributes to the rehabilitation of patients with oral-sinus-nasal sequelae, which in turn affect important functions such as chewing, swallowing, and speech. The prosthetic rehabilitation with implant-retained dentures is a suitable treatment option. The purpose of this study was to verify, by using a photoelastic analysis, the stress distribution in implant-retained palatal obturator dentures (relined or not) associated with different attachment systems (O-ring, bar-clip, and bar-clip associated with distally placed O-rings). Two photoelastic models were obtained from an experimental maxillary cast presenting an oral-nasal communication. One model had two 13-mm length implants placed on the left region. A total of eight colorless maxillary obturators were fabricated and subsequently four of them were relined with soft silicone soft, and three had attachment systems associated. The assembly (model/attachment system/prosthesis) was positioned in a circular polariscope and a 100-N load was applied at 10 mm/s. The results showed that the denture relining influenced the distribution and amount of stress on the models. The O-ring group displayed the lowest stress levels, followed by bar-clip system associated with distally placed O-rings and bar-clip groups. (C) 2012 Society of Photo-Optical Instrumentation Engineers (SPIE). [DOI: 10.1117/1.JBO.17.6.061203]
Keywords: dental implant; maxillectomy; photoelastic; denture liners